Islamic Studies Berbasis Research - Damanhuri, Aji (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2011)
The research aims at re-motivating research tradition in Islamic studies by developing scientific and rational epistemological framework, acceptance to critiques, comprehensiveness, multidimensional, and applicative to solve the problems of universal humanity. This research employs descriptive philosophical method and interpretative analysis by portraying the reality of contemporary Islamic studies and analyzing them using the already developed Islamic epistemological framework. It is expected that, from motivations written in this research, cosmopolitan Islamic civilization, which respects diversity, pluralism, human rights, women?s dignity, is ecologically sensitive, and is full of love with other people and other creatures of God would emerge.